Social Media: Problematics of Fashion Character Changes in Adolescents - Ridwan Kusumah Wijaya; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this era of globalization, technological developments are very rapid, almost everything can be accessed via the internet. The presence of social media can cause most teenagers to directly change their own behavior patterns that have an impact on the environment around them. The approach used in this research is a qualitative approach with a qualitative descriptive method. To collect data in the field researchers used interviews, observation and documentation. Lifestyle changes students are closely related to the times and technology because technology and times that are increasingly developing and sophisticated will create the development and application of lifestyles such as dress styles, speech styles, language styles, and consumptive lifestyles in everyday life. From the results of the interviews it can be concluded that advertising is a supporting factor for the modern lifestyle adopted by students. All of the respondents interviewed said that the advertisement illustrates how the world is currently developing, and also has a positive impact on those who sell online. The progress of the times in the field of knowledge and technology has had a major influence on the people's economy, marked by the easier it is for people to communicate, so that fulfilling their wants and needs is easier and more practical.